Genetic Variation and Geographic Differentiation Among Populations of the Nonmigratory Agricultural Pest Oedaleus infernalis (Orthoptera: Acridoidea) in China. Issue 1 (24th October 2015) - Sun, Wei; Dong, Hui; Gao, Yue-Bo; Su, Qian-Fu; Qian, Hai-Tao; Bai, Hong-Yan; Zhang, Zhu-Ting; Cong, Bin
Abstract : The nonmigratory grasshopper Oedaleus infernalis Saussure (Orthoptera : Acridoidea) is an agricultural pest to crops and forage grasses over a wide natural geographical distribution in China. The genetic diversity and genetic variation among 10 geographically separated populations of O. infernalis was assessed using polymerase chain reaction-based molecular markers, including the intersimple sequence repeat and mitochondrial cytochrome oxidase sequences. A high level of genetic diversity was detected among these populations from the intersimple sequence repeat ( H : 0.2628, I : 0.4129, H s : 0.2130) and cytochrome oxidase analyses ( H d : 0.653). There was no obvious geographical structure based on an unweighted pair group method analysis and median-joining network. The values of F ST, θ II, and Gst estimated in this study are low, and the gene flow is high ( N m  > 4). Analysis of the molecular variance suggested that most of the genetic variation occurs within populations, whereas only a small variation takes place between populations. No significant correlation was found between the genetic distance and geographical distance. Overall, our results suggest that the geographical distance plays an unimpeded role in the gene flow among O. infernalis populations.